A Survey on Capacitive based CO2 Gas Sensor - Shwetha H.R, Ms.; Rudraswamy S. B., Dr (International Journal of Engineering and Technology, 2018)
In this current scenario, different sensing mechanisms are investigated and used in detection of hazardous gases. A review of capacitive type gas sensor for detection is presented in this paper. Even though there are very limited numbers of publications on capacitive based gas sensors, detection of CO2 based on change in dielectric constant it shows good sensing mechanism with sensitivity and high reliability.Â